The June 1986 eruption of Bezymyannyi - Maksimov A.P.; Firstov P.P.; Girina O.A.; Malyshev A.I. (My University, 1992)
This paper presents the results of visual observations, particle-size analysis, seismological observations, and acoustic measurements carried out during a small-magnitude eruption of Bezymyannyi in June 1986. A mlodel is proposed for the mechanism of the eruption. A specific character of the eruption is explained by a deeper localization of a gas-rich aagia portion in the conduit,
Keywords: 38.37.25 Вулканология; Безымянный